Colloids Versus Albumin in Large Volume Paracentesis to Prevent Circulatory Dysfunction: Evidence-based Case Report - Felix F Widjaja; Paramita Khairan; Telly Kamelia; Irsan Hasan (Acta Medica Indonesiana)
Large volume paracentesis may cause paracentesis induced circulatory dysfunction (PICD). Albumin is recommended to prevent this abnormality. Meanwhile, the price of albumin is too expensive and there should be another alternative that may prevent PICD. This report aimed to compare albumin to colloids in preventing PICD. Search strategy was done using PubMed, Scopus, Proquest, dan Academic Health Complete from EBSCO with keywords of “ascites”,  “albumin”, “colloid”, “dextran”, “hydroxyethyl starch”, “gelatin”, and “paracentesis  induced  circulatory  dysfunction”. Articles was limited to randomized clinical trial and meta-analysis with clinical question of “In hepatic cirrhotic patient undergone large volume paracentesis, whether colloids were similar to albumin to prevent PICD”. We found one meta-analysis and four randomized clinical trials (RCT). A meta analysis showed that albumin was still superior of which odds ratio 0.34 (0.23-0.51). Three RCTs showed the same results and one RCT showed albumin was not superior than colloids. We conclude that colloids could not constitute albumin to prevent PICD, but colloids still have a role in patient who undergone paracentesis less than five liters.